Protein Intake, Prognostic Nutritional Index and Quality of Life in Head and Neck Cancer Patients Undergoing Radiotherapy - Andry Kelvianto; Fiastuti Witjaksono; Sri Mutya Sekarutami (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: It has not been well understood whether the quality and quantity of protein intake could affect the quality of life. Quality of life is associated with nutritional status, but the usage of prognostic nutritional index (PNI) to reflect quality of life of head and neck cancer patients undergoing radiotherapy also still has not been widely studied.METHODS: A cross sectional study was performed in 61 head and neck cancer patient undergoing radiotherapy. The quantity and quality of protein intake were obtained using semiquantitative food frequency questionnaire (FFQ) which was analized by analyzed using Nutrisurvey 2007, PNI was obtained using a calculation of Onodera’s formula based on laboratory data of serum albumin and total lymphocyte count (TLC), and domains of quality of life were obtained from the interview of European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Core Questionnaire (QLQ-C30) and EORTC Quality of Life Head and Neck module (QLQ-H&N35) and then calculated to get each domain’s score on quality of life.RESULTS: Patient’s median of total protein intake was 1.42 (0.26-4.11) g/kg/day. The median of PNI was 45.9 (29.4- 54.2). Quantity of protein intake was significantly correlated with several symptoms domain of quality of life. PNI was also significantly correlated with one functional domain and two symptom domains of quality of life. This study did not show a significant correlation between quantity and quality of protein intake with PNI.CONCLUSION: PNI has the potential to reflect quality of life of head and neck cancer patients. Future studies might be beneficial to show the usage of PNI to reflect quality of life, especially involving the progressivity of quality of life.KEYWORDS: animal protein, chemoradiotherapy, cachexia, quality of life